2022
DOI: 10.1021/jacs.2c10196
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Formally NiIV–Oxo Complex with a Triplet Ground State and Application in Oxidation Reactions

Abstract: High-valent first-row transition-metal–oxo complexes are important intermediates in biologically and chemically relevant oxidative transformations of organic molecules and in the water splitting reaction in (artificial) photosynthesis. While high-valent Fe– and Mn–oxo complexes have been characterized in detail, much less is known about their analogues with late transition metals. In this study, we present the synthesis and detailed characterization of a unique mononuclear terminal Ni–O complex. This compound,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…Notably, ZN–O–A-7 catalyzed dehydrogenation of toluene in the presence of oxygen (10 bar) at 100 °C failed to produce any desired products. High-valent nickel–oxo (Ni III –oxo/peroxo and Ni IV –oxo) species are believed to be possible intermediates in a number of nickel-based oxidation reactions involving discrete homogeneous nickel-based catalysts. , Meanwhile, the generation of these species in the presence of oxygen is more feasible in the case of lower oxidation states (0, +1) of nickel in comparison to Ni­(II). , In the present case, the generation and stability of these active species are expected to be inhibited by strong charge transfer between Ni–NiO–ZnO heterojunctions in ZN–O–A-7 . For catalytic activity, toluene was used as the reagent and solvent, and its reaction was performed in the presence of TBHP (200 μL 5–6 M decane solution) at 110 °C for 12 h. The conversion of the reaction was calculated based on the amount of TBHP used for the reaction with decane as the internal standard.…”
Section: Results and Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Notably, ZN–O–A-7 catalyzed dehydrogenation of toluene in the presence of oxygen (10 bar) at 100 °C failed to produce any desired products. High-valent nickel–oxo (Ni III –oxo/peroxo and Ni IV –oxo) species are believed to be possible intermediates in a number of nickel-based oxidation reactions involving discrete homogeneous nickel-based catalysts. , Meanwhile, the generation of these species in the presence of oxygen is more feasible in the case of lower oxidation states (0, +1) of nickel in comparison to Ni­(II). , In the present case, the generation and stability of these active species are expected to be inhibited by strong charge transfer between Ni–NiO–ZnO heterojunctions in ZN–O–A-7 . For catalytic activity, toluene was used as the reagent and solvent, and its reaction was performed in the presence of TBHP (200 μL 5–6 M decane solution) at 110 °C for 12 h. The conversion of the reaction was calculated based on the amount of TBHP used for the reaction with decane as the internal standard.…”
Section: Results and Discussionmentioning
confidence: 82%
“…Highvalent nickel−oxo (Ni III −oxo/peroxo and Ni IV −oxo) species are believed to be possible intermediates in a number of nickelbased oxidation reactions involving discrete homogeneous nickel-based catalysts. 45,46 Meanwhile, the generation of these species in the presence of oxygen is more feasible in the case of lower oxidation states (0, +1) of nickel in comparison to Ni(II). 47,48 In the present case, the generation and stability of these active species are expected to be inhibited by strong charge transfer between Ni−NiO−ZnO heterojunctions in ZN−O−A-7.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4−6 The molecular complex [Ni-(TAML)(O)(OH)] 3− (TMAL = tetraamido macrocyclic ligand) has been used for the oxidation of organic compounds like thioanisole and styrene derivatives in which Ni III -oxyl was involved in the oxidation process. 7 Also, the rich chemistry of metal−oxo complexes inspired the synthesis of C−H oxidation catalysts. 8,9 The previous report showed that chelating ligands could enhance the stability of metal−oxo intermediates, thereby enabling precise modulation of chemo-and regioselectivity during the electron-transfer and oxo-transfer stages.…”
Section: ■ Introductionmentioning
confidence: 99%
“…, cobalt and nickel) after group 8 in the periodic table of elements are extensively employed. 29–49 Due to the oxo-wall, an additional electron locates in an antibonding orbital to convert a metal–oxo species to a metal–oxyl species, which makes the active species containing metals after group 8 more robust. 50–52 In this text, we focus on the elusive active species and reaction mechanism of nickel( ii )-mediated hydrocarbon oxidations with meta -chloroperbenzoic acid ( m CPBA).…”
Section: Introductionmentioning
confidence: 99%
“…50–52 In this text, we focus on the elusive active species and reaction mechanism of nickel( ii )-mediated hydrocarbon oxidations with meta -chloroperbenzoic acid ( m CPBA). 29–49…”
Section: Introductionmentioning
confidence: 99%